2001
DOI: 10.1203/00006450-200110000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Development in The Netherlands 1965–1997

Abstract: We investigated pubertal development of 4019 boys and 3562 girls Ͼ8 y of age participating in a cross-sectional survey in The Netherlands and compared the results with those of two previous surveys. Reference curves for all pubertal stages were constructed. The 50th percentile of Tanner breast stage 2 was 10.7 y, and 50% of the boys had reached a testicular volume of 4 mL at 11.5 y of age. Median age at menarche was 13.15 y. The median age at which the various stages of pubertal development were observed has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
227
2
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(260 citation statements)
references
References 24 publications
20
227
2
11
Order By: Relevance
“…Therefore, analysis of variance within and across generations is the key issue for answering the question of whether or not it is necessary to control for phase of sexual maturity. 20 2) indications that, for the population as a whole, countries such as the USA and Holland do not currently exhibit the tendency towards reducing age at menarche; 21,22 3) in Brazil, the reduction in age at menarche is estimated at 2.4 to 2.7 months per decade. 23,24 Taken together this evidence allows for the assumption that, in the case of Brazil, the impact of intergenerational variation (including variations within and between individuals) should not distort the curves presented here.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, analysis of variance within and across generations is the key issue for answering the question of whether or not it is necessary to control for phase of sexual maturity. 20 2) indications that, for the population as a whole, countries such as the USA and Holland do not currently exhibit the tendency towards reducing age at menarche; 21,22 3) in Brazil, the reduction in age at menarche is estimated at 2.4 to 2.7 months per decade. 23,24 Taken together this evidence allows for the assumption that, in the case of Brazil, the impact of intergenerational variation (including variations within and between individuals) should not distort the curves presented here.…”
Section: Resultsmentioning
confidence: 99%
“…the 10th to 90th centile range ( Table 2). Distortion of the variance was negative in the studies involving subjects born before the 1970s (Jeurissen, 1969;Vercauteren and Susanne, 1985) and was found to be positive in several more recent studies since 1980 (Roelants et al, 2009;Talma et al, 2013;Mul et al, 2001). Consequently (Fig.…”
Section: Variable Pattern Of Pubertal Timing Depending On Pubertal Enmentioning
confidence: 88%
“…This finding was in accordance with our national survey on pubertal development between 1965 and 1997, which showed that the timing of the occurrence of the various stages of pubertal development had stabilized between 1980 and 1997. This despite the general trend of increasing overweight and obesity in the same population (22).…”
Section: Anthropometric Measurementsmentioning
confidence: 89%